2015
DOI: 10.1186/s13717-015-0032-2
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating within- and between-patch resource selection in identification of critical habitat for brood-rearing greater sage-grouse

Abstract: Introduction: Incorporating information on animal behavior in resource-based predictive modeling (e.g., occurrence mapping) can elucidate the relationship between process and spatial pattern and depict habitat in terms of its structure as well as its function. In this paper, we assigned location data on brood-rearing greater sage-grouse (Centrocercus urophasianus) to either within-patch (encamped) or between-patch (traveling) behavioral modes by estimating a movement-based relative displacement index. Objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…While movement patterns are often used to distinguish active phases from rest, or search behavior from traveling (van Beest & Milner, ; Dzialak, Olson, Webb, Harju, & Winstead, ), identifying these behavioral states typically relies on more complicated modeling procedures to detect potential underlying mechanisms within behavior identification (Jonsen, Myers, & James, ; Kerk et al., ). Considerable progress has been made in developing methods that can categorize behaviors based on simple movement metrics (Edelhoff, Signer, & Balkenhol, ).…”
Section: Introductionmentioning
confidence: 99%
“…While movement patterns are often used to distinguish active phases from rest, or search behavior from traveling (van Beest & Milner, ; Dzialak, Olson, Webb, Harju, & Winstead, ), identifying these behavioral states typically relies on more complicated modeling procedures to detect potential underlying mechanisms within behavior identification (Jonsen, Myers, & James, ; Kerk et al., ). Considerable progress has been made in developing methods that can categorize behaviors based on simple movement metrics (Edelhoff, Signer, & Balkenhol, ).…”
Section: Introductionmentioning
confidence: 99%
“…To test whether northern pintails preferred certain rice paddies over others, we developed RSFs using a use vs. availability design (e.g. [51]). We defined available rice paddies as those that contained surface water at the time of selection.…”
Section: Methodsmentioning
confidence: 99%
“…Different behavioral states influence a female's activity levels and time spent in each activity. Females expressing different behavior may show differences in habitat selection throughout the day (Roever et al 2014) as suggested by previous research showing differences in sage-grouse habitat selection during different times of the day (Dunn andBraun 1986, Sveum et al 1998), at night (Dzialak et al 2011), and within and between patches (Dzialak et al 2015). Aside from changing behavioral state, the time spent therein may change throughout the day (Walker et al 2006).…”
mentioning
confidence: 87%
“…Due to variation in sage-grouse productivity across years from environmental stochasticity (Taylor et al 2012), survival of broodless females (i.e., females without a brood) may become even more important during years of low reproductive success. Different sage-grouse reproductive states can influence habitat selection (Gregg et al 1993, Kirol et al 2015, Smith et al 2018) but little is known about how sage-grouse behavior influences habitat selection (but see Dzialak et al 2015).…”
mentioning
confidence: 99%